Establishing cognitive baseline in three generations: Framingham Heart Study. Issue 1 (24th March 2023) - Yang, Jin; Ang, Ting Fang Alvin; Lu, Sophia; Liu, Xue; Devine, Sherral; Au, Rhoda; Liu, Chunyu
Abstract: Introduction: Generational changes warrant recalibrating normative cognitive measures to detect changes indicative of dementia risk within each generation. Methods: We performed linear regressions to compare eight neuropsychological (NP) tests among three‐generation cohorts at baseline in Framingham Heart Study (FHS, n = 4787) and conducted Cox regressions to investigate the relationships of NP tests with generation‐specific dementia risk. Results: The FHS second and third generations performed better than the first generation for seven NP tests (0.14–0.81 standard deviation improvement, P ≤ .001) while the second and third generations performed similarly for six of eight NP tests ( P > .05). One standard deviation better performance was associated with a higher reduction in incident dementia risk in the second than the first generation (35% vs. 24%, P interaction = .02) for the similarities test. Discussion: Our findings suggest cohort‐based norms are needed for cognitive assessment for the diagnosis of cognitive impairment and dementia.